Development of functional dark chocolate by incorporating flaxseed (Linum usitatissimum) oil and honey with improved organoleptic and textural attributes - Singh D.; Tripathi A.D.; Adhikari K.S.; Paul V. (My University, 2025)
Background: Chocolate is one of the most consumable fast-moving consumer goods (FMCG), possessing many health benefits. The present study was envisaged to develop dark chocolate incorporated with flaxseed (Linum usitatissimum) oil and honey. Flaxseed oil contains omega-3 fatty acid which is useful in heart disease, arthritis, inflammatory and autoimmune diseases, and cancer, whereas honey acts as an antioxidant. Objective: The objective of this study was to develop functional dark chocolate with improved organoleptic, textural and functional attributes by optimizing the ingredients levels such as flaxseed oil and honey and its further validation for quality improvement. Methods: The chocolate composition was optimized by selecting two variables including flaxseed oil (1-2.5g) and honey (10-15g) at 3 levels in central composite rotatable design (CCRD) by using Design-Expert version 11 software tool. Results: After optimization, the best-predicted formulation comprising flaxseed oil 2.37% (w/w) and honey 15% (w/w) showed best sensorial score (p <0.05) with desirability 0.826. Conclusion: Physicochemical analysis of optimized formulation showed significant improvement in organoleptic attributes (p <0.05) with a significant increase of 10.22% (p <0.05) in antioxidant activity in comparison to control. © 2020 Bentham Science Publishers.